SIMPLE ADDITIVE WEIGHTING SEBAGAI MODEL PENGAMBILAN KEPUTUSAN PENERIMA BANTUAN DESA DI KECAMATAN KEDONDONG - Supriyanto, Supriyanto (Jurnal TAM (Technology Acceptance Model), 2024)
The selection of village aid recipients in Kedondong District requires an objective and transparent system to ensure that assistance is properly distributed. One method that can be used is Simple Additive Weighting (SAW), which enables decision-making based on weighted criteria. This study aims to apply the SAW method in the selection process of village aid recipients by considering several criteria, such as income level, number of dependents, housing conditions, and employment status. The results show that the SAW method provides more accurate and fair outcomes compared to conventional methods, as it ranks recipients based on systematically calculated final scores. Thus, the SAW method can serve as a model for supporting more objective and transparent decision-making in the distribution of village aid in Kedondong District.